Conflict and Crisis Communication : Principles and Practice. - Ireland, Carol A. (Taylor and Francis, 2012)
Conflict and crisis communication is the management of a critical incident which has the potential for resolution through successful negotiations. This can include negotiating with individuals in crisis, such as those threatening self-harm or taking individuals hostage as part of emotional expression, and also critical incidents such as kidnapping and terrorist activities. By focusing on the empirical and strong theoretical underpinnings of critical incident management, and including clear demonstrations of the practical application of conflict and crisis communication by experts in t.